Do Cell Group Independent Activities Impact Students’ Score Achievement? - Melania Wiannastiti (Humaniora, 2012)
There are many methods offered to teach in a university level. In teaching English Entrant, one course of general English courses at Binus University, a lecturer needs to choose an appropriate method. One appropriate method used is cooperative learning one. In this method, students in a class are divided into groups called cell group. In the cell group, they needed to do some activities independently. Based on the above reason, this paper aimed to find out whether the cell group independent activities impact the students’ score achievement in reading and listening. The data for the paper was the students’ scores of listening and reading they gained in mid semester test, final test English Entrant and the weekly reports of students’ cell activities. The method used to analyze the data was percentage number to compare the scores and cell group activities for both listening and reading. The result shows that there was a significant higher achievement of the students in both listening and reading either the number of cell group activities 1-3 or 4-6 times of activities. It could be concluded that the cell group activities gave good impact in supporting students to achieve high score in reading or listening.